(untitled) (Bangladesh Journal of Medical Science, 2016)
Objective: According to WHO, about 30 % of people in the world are overweight that allows to characterize this disease as a new non-infection epidemic of the XXI century. More than 500 million people in the world are overweight and 250 million are obese. There is a clear tendency to increasing of alimentary obesity among people with different age, sex and nationality. The aim of the study is to investigate the thiol-disulfide homeostasis in liver tissue, adipose tissue and erythrocytes in the pathogenesis of experimental alimentary obesity. Materials and methods: 60 males, non-liner, white rats around 3 months of age with alimentary obesity were examined during the study. Experimental obesity was modeled by administering of sodium glutamate to the feed mixture in a ratio of 0.6:100.0 and adding high-calorie diet. The glutathione redox-system activity in erythrocytes, liver and adipose tissue were analyzed by the level of reduced glutathione (GSH), oxidized glutathione (GSSG), glutathione reductase (GR) and glutathione peroxidase (GP) activity. Results and Discussion: The data indicate a decrease in GSH level within 14 days of the experiment in all investigated tissues. The same trend was observed in animals on 28th day of the experiment: GSH index decreased in blood, adipose tissue and liver (P<0.05). The index of GSSG have increased on 28th day of the experiment in all investigated tissues vs control group (P<0.05). The ratio of the reduced and oxidized forms of glutathione contents was much lower vs control group in all the studied tissues within 28 days of the experiment. During additional investigation of the activity of thiol-disulfide system enzymes it was found that reducing the concentration of GSH in rats with alimentary obesity was due to the lack of thiol-disulfide system enzymes activity: GP and GR, which take part in the regeneration of GSH from GSSG. Conclusion: experimental alimentary obesity is characterized by a reduced redox state in blood, adipose and liver tissues, which is determinative in increasing the free radical reactions and accumulation of highly toxic lipoperoxides in the tissue substrates. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.419-423